Change of direction and linear speed relation to functional ability and joint mobility in Polish U19 volleyball and basketball 3 × 3 national teams - Czyznielewska, Zuzanna; Gabrys, Tomasz; Yagin, Fatma Hilal; Cepicka, Ladislav (Frontiers in Sports and Active Living, 2024)
The purpose of this study was to determine the extent of differences in the level of change in linear speed and velocity in the modified change of direction test (COD) and to determine the relationship between speed deficits resulting from changes of direction and functional performance between groups of Polish U19 Volleyball National Team and Polish Women's Basketball 3x3 National Team. A total of 23 athletes: 12 volleyball players (age:18±0years; body height:183±7cm; body weight:70±8kg) and 11 basketball players (age:26±4 years; body height:180±6cm; body weight:73±10kg) participated in the study. Athletes were tested for the following measures: Functional Movement Screen test (FMS), dynamic balance test Y-Balance, joints range of motion measurements, maximal sprint test (14m), modified COD test (14m) and change of direction deficit (CODD). A value of p < 0.05 was considered statistically significant. There was no significant correlation between sprint and CODD results in basketball team. In volleyball team there was a positive and significant correlation between COD, sprint and CODD. There was a negative and significant correlation between Y-Balance scores and sprint test results in the basketball team. Basketball team had a positive significant correlation between hip rotations and COD results. There was a negative significant correlation between shoulder movements and COD and CODD results in volleyball team.